ИНГЛИС ҲӘМ ҚАРАҚАЛПАҚ ЕРТЕКЛЕРИНДЕ ЭПИКАЛЫҚ ЎАҚЫТ, ЭПИКАЛЫҚ МӘКАН ҲӘМ ЭПИКАЛЫҚ ҚАҲАРМАНЛАР - Сайтова, З.К. (SCIENCE and SOCIETY, 2022)
The article compares English and Karakalpak folk tales. And also, in fairy tales, the epic hero, epic territory, epic time are studied theoretically and practically.Very powerful epic heroes also take part in fairy tales. One hero confronts thousands of enemies. For example, in the Karakalpak folk tale "Abat-batyr" the hero fought alone with thousands of royal soldiers and defeated them. In the Karakalpak folk tale "Brave Boy", the protagonist defeats the giant cannibals. The hero brings the kidnapped girls. It reveals the character of an epic hero. The narrator expressed the strength and character of the protagonist through hyperbole.